2006
DOI: 10.1111/j.1525-1438.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Fas gene promoter -670 polymorphism in gynecological cancer

Abstract: Single-nucleotide polymorphism at -670 of Fas gene promoter (A/G) was examined in a total of 354 blood samples from normal healthy women and gynecological cancer patients. They consisted of 95 normal, 83 cervical, 108 endometrial, and 68 ovarian cancer cases. Eighty-three patients with cervical cancer had statistically higher frequency of GG genotype and G allele than 95 controls (P= 0.0353 and 0.0278, respectively). There was no significant difference in the genotype or allele prevalence between control subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 14 publications
0
29
1
1
Order By: Relevance
“…It has been suggested that the reduction of Fas membrane receptor would reduce apoptosis and be associated with a malignant potential. 9,16,17 However, our results may be in accordance with the recently published studies suggesting the opposite hypothesis. [41][42][43][44] Fas exists as membrane-bound and soluble forms with opposite roles on triggering apoptosis.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…It has been suggested that the reduction of Fas membrane receptor would reduce apoptosis and be associated with a malignant potential. 9,16,17 However, our results may be in accordance with the recently published studies suggesting the opposite hypothesis. [41][42][43][44] Fas exists as membrane-bound and soluble forms with opposite roles on triggering apoptosis.…”
Section: Discussioncontrasting
confidence: 47%
“…A significantly associated risk was found for FAS À670 A/G polymorphism in bladder, 13 cervical cancer, 11,16,22 cutaneous malignant melanoma, 12 esophageal and head and neck squamous cell carcinoma, 15,21 lung and nasopharyngeal cancer. 9,17,20 We analyzed the frequency of FAS genotypes in the normal control population.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although evidence of an association between FAS/FASL polymorphisms and cervical cancer risk has been reported, the findings remain controversial (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Therefore, we performed a meta-analysis of all published studies on the association between the FAS/FASL polymorphisms and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Fas gene mutations and single-nucleotide polymorphisms (SNP) in the promoter region have also been described for endometrial cancers (Ueda et al 2006). However, the impact of these mutations on response to therapy and prognosis is not well defined and is yet to be understood in endometrial cancer.…”
Section: The Extrinsic Death Receptor Pathwaymentioning
confidence: 99%